Comparison of Health Care Costs Between Claimants and Nonclaimants in the No-Fault Compensation System of Finland - Järvelin, Jutta (J Patient Saf, 2019)
OBJECTIVES: If patients experience health care–related adverse events, they may claim for compensation. Adverse events of claimants are generally more severe and presumably involve higher health care costs than those of nonclaimants. The aim of this study was to estimate the cost differential between claimants and nonclaimants in the no-fault system in Finland. METHODS: We compiled register data on patients having had coronary artery bypass grafting (CABG, n = 20,500), total hip arthroplasty (n = 17,506), or knee arthroplasty (TKA, n = 18,512) and calculated risk-adjusted cost differentials by using a gamma distributed, log-linked generalized linear model. The explained variable comprised costs, whereas the main explanatory variables were whether the patient filed a claim and whether he or she received compensation. RESULTS: Uncompensated claimants had higher admission costs (CABG, €3660, 29%; total hip arthroplasty, €418, 5%; TKA, €359, 4%) compared with nonclaimants, whereas the differential between compensated claimants and uncompensated claimants was statistically insignificant. Significant associations emerged concerning CABG 1-year costs: uncompensated claimants had €12,990 (71%) higher costs than nonclaimants, whereas compensated claimants had €6388 (20%) higher costs than uncompensated claimants. CONCLUSIONS: Although the precise cost differentials may be specific to Finland, the implications may apply also to other countries. (1) Excess costs of claimants should motivate efforts to reduce adverse events. (2) Analyses of claims to improve patient safety should not be restricted to compensated claims only but should equally concern uncompensated claims. A further implication regarding Finland is that additional approaches to identify and report adverse events are necessary.